Effects of encapsulated organic acids and essential oils on intestinal barrier, microbial count, and bacterial metabolites in broiler chickens - Yang, Xin; Liu, Yanli; Yan, Fang; Yang, Chengbo; Yang, Xiaojun (Poultry science, 2019)
The aim of this study was to evaluate a combination diet of organic acids and essential oils on epithelial restitution, intestinal microflora, and volatile fatty acids in broiler chickens. A total of 144 1-day-old male chicks (Cobb 500) were allotted to 3 treatment groups consisting of 6 replicates with 8 birds per replicate. The dietary treatments were as follows: control group (CON, basal diet), antibiotics group (ANT, control + 0.15 g/kg enramycin), and addition group (EOA, control + 0.30 g/kg encapsulated organic acids and essential oils). Compared to the CON group, the EOA group showed a higher feed conversion ratio (FCR) (P < 0.05) at day 42. The ANT group showed the lowest count of Lactobacillus spp. (P < 0.05) and the highest count of Escherichia coli (P < 0.05) in the ileal digesta. Birds that were fed the EOA-supplemented diet had decreased populations of E. coli (P < 0.05). Compared with the ANT group, supplementation with EOA tended to reduce the pH of jejunal digesta (P = 0.079) and ileal digesta (P = 0.078) but significantly increased the concentration of butyric acid (P < 0.05) and tended to increase the concentrations of acetic acid (P = 0.087) and total short-chain fatty acids (SCFA; P = 0.098) in the ileal digesta. The EOA group showed higher sucrase and maltase activities of jejunal mucosa (P < 0.05) than those in the other groups. The EOA supplementation increased (P < 0.05) claudin-1 mRNA expression in the jejunum. Compared with the other groups, enramycin supplementation significantly reduced jejunal mucosa sIgA (P < 0.05) and down-regulated Mucin-2 and TLR2 mRNA relative expression (P < 0.05) in the jejunal mucosa of broiler chickens. Both EOA and enramycin contribute beneficially to FCR because of their antimicrobial action. EOA may reduce harmful bacteria and promote digestive enzyme activity and higher concentrations of SCFA. In contrast, enramycin may inhibit the growth of beneficial bacteria and reduce the need for intestinal mucosal barrier function.